The Impact of Celebrity Instagram Endorsement to Brand Image - Novha Sary, Nadiya; Chaerudin, Rendra (Journal of Innovation, Business and Entrepreneurship, 2018)
Abstract. There are so Small and Medium Enterprises in Indonesia are doing business in fashion industry. This creates startups should work harder in doing promotion their products and brands. One way to attract customers is with advertisement. Effective advertising can done with endorsement, with support that uses people known to many as a celebrity.Currently, someone who has popularity and followers than 20,000 in social media instagram also can be said celebrity instagram. Social media such as instagram is very concerned by world community especially Indonesian. Instagram is the second most visited social media after youtube. This creates a great opportunity for startups who want to promote their product or brand to its customers through Instagram social media.The purpose of this study is to determine the influence of celebrity instagram endroser to brand image. This research is expected to be useful and implemented for Small Medium Enterprises especially Iluvia Indonesia. This research used quantitative method by using non-probability sampling data collection technique using slovin formula with error 10%. The analysis used is a simple linear regression to test the hypothesis. The results of this study indicate that the use of celebrity instagram endorsement is classified as having a major influence to improve the brand image.Â Keywords:Â  Impact, Effective advertising, Celebrity Instagram, Endorsement, Brand Image.